The pathway of melatonin biosynthesis in common wheat (Triticum aestivum). Issue 2 (12th December 2022) - Chen, Jie; Zhang, Yueqi; Yin, Huanran; Liu, Wei; Hu, Xin; Li, Dongqin; Lan, Caixia; Gao, Lifeng; He, Zhonghu; Cui, Fa; Fernie, Alisdair R.; Chen, Wei
Abstract: Melatonin (Mel) is a multifunctional biomolecule found in both animals and plants. In plants, the biosynthesis of Mel from tryptophan (Trp) has been delineated to comprise of four consecutive reactions. However, while the genes encoding these enzymes in rice are well characterized no systematic evaluation of the overall pathway has, as yet, been published for wheat. In the current study, the relative contents of six Mel‐pathway‐intermediates including Trp, tryptamine (Trm), serotonin (Ser), 5‐methoxy tryptamine (5M‐Trm), N ‐acetyl serotonin (NAS) and Mel, were determined in 24 independent tissues spanning the lifetime of wheat. These studies indicated that Trp was the most abundant among the six metabolites, followed by Trm and Ser. Next, the candidate genes expressing key enzymes involved in the Mel pathway were explored by means of metabolite‐based genome‐wide association study (mGWAS), wherein two TDC genes, a T5H gene and one SNAT gene were identified as being important for the accumulation of Mel pathway metabolites. Moreover, a 463‐bp insertion within the T5H gene was discovered that may be responsible for variation in Ser content. Finally, a ASMT gene was found via sequence alignment against its rice homolog. Validations of these candidate genes were performed by in vitro enzymatic reactions using proteins purified following recombinant expression in Escherichia coli, transient gene expression in tobacco, and transgenic approaches in wheat. Our results thus provide the first comprehensive investigation into the Mel pathway metabolites, and a swift candidate gene identification via forward‐genetics strategies, in common wheat.